Emergence and development of water legislation in Uzbekistan - Khayitov Khasan Shermatovich (Periodica Journal, 2022)
The emergence and development of water legislation can be classified into four stages. The first stage is the stage of formation of water legal norms and rules in ancient times. The most important legal provisions for the protection of water resources of this stage can be found in the “Avesto”, the sacred book of the ancient Zoroastrians
Keywords: emergence; development; legislation; classified